DESIGNING WEB-BASED LEARNING MEDIA TO SUPPORT NARRATIVE TEXT READING COMPREHENSION - Isma Syafitri; Yohanes Gatot Sutapa Yuliana; Urai Salam (PROJECT (Professional Journal of English Education), 2024)
This study is aimed at designing a web-based learning media and finding its appropriateness in supporting the ninth-grade students’ narrative text reading comprehension in SMPN 16 Singkawang. The ADD design from ADDIE was employed in this study, with observation, interview, and expert validation as the data collection technique. The results of the observation and interview revealed the need for learning media to address the difficulties in comprehending narrative texts among the students. Expert validations revealed that the designed product was very valid in terms of media and material design, with percentages of 85.3% and 96.3%, respectively. The final product includes multimedia and four reading texts translated and adapted from Singkawang local folktales. In conclusion, the web-based learning media was considered as an appropriate medium to be utilized by the students.